2011
DOI: 10.1074/jbc.m110.158477
|View full text |Cite
|
Sign up to set email alerts
|

N-cadherin Regulates p38 MAPK Signaling via Association with JNK-associated Leucine Zipper Protein

Abstract: Synaptic loss, which strongly correlates with the decline of cognitive function, is one of the pathological hallmarks of Alzheimer disease. N-cadherin is a cell adhesion molecule essential for synaptic contact and is involved in the intracellular signaling pathway at the synapse. Here we report that the functional disruption of N-cadherin-mediated cell contact activated p38 MAPK in murine primary neurons, followed by neuronal death. We further observed that treatment with A␤ 42 decreased cellular N-cadherin ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 41 publications
(46 reference statements)
1
53
0
Order By: Relevance
“…60 Moreover, dissociation of N-cadherin-mediated synaptic contact by Ab has been proposed to cause neuronal cell death, synaptic loss and tau phosphorylation in AD brain. 61 Two affected siblings in family ND6 show the presence of FAD-CNV6, a 0.73-Mb intergenic gain in CN. EPHA6 is located 0.33-Mb telomeric and the only described gene in close proximity.…”
Section: Rare Autosomal Cnvs In Eo-fad Bv Hooli Et Almentioning
confidence: 99%
“…60 Moreover, dissociation of N-cadherin-mediated synaptic contact by Ab has been proposed to cause neuronal cell death, synaptic loss and tau phosphorylation in AD brain. 61 Two affected siblings in family ND6 show the presence of FAD-CNV6, a 0.73-Mb intergenic gain in CN. EPHA6 is located 0.33-Mb telomeric and the only described gene in close proximity.…”
Section: Rare Autosomal Cnvs In Eo-fad Bv Hooli Et Almentioning
confidence: 99%
“…A increases NMDAR activity [143,144] and induces inwards Ca 2+ current and neurotoxicity [145]. Reciprocally, NMDAR activation stimulates A production [146][147][148] and A associated synaptic loss may be NMDAR-dependent [149].…”
Section: Cognitive Impairment and Dementiamentioning
confidence: 99%
“…Sperm-associated antigen 9 (SPAG9) was originally identified as a novel member of the CT antigen family, and functions as a scaffolding protein involved in the activation of the c-Jun NH2-terminal kinase (JNK) signaling pathway (8)(9)(10)(11)(12). Previous studies have reported that SPAG9 is overexpressed in various types of human cancer, including breast, thyroid and cervical cancer, and colorectal carcinoma (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%